Carbon nanotubes : reinforced metal matrix composites.: reinforced metal matrix composites. (2021) - Nieto, Andy; Agarwal, Arvind; Lahiri, Debrupa; Bisht, Ankita; Bakshi, Srinivasa Rao
No abstract available